Level of immunoglobulins with acute and chronic bacterial rhinosinusitis - Al Hariri, Mahmoud Jоmaa; Semenenko, S.; Furman, R. (Actual Dentistry, 2018)
Purpose: to study the concentration of immunoglobulin A (secretory and general) against the background of basic therapy and against the background of the imunomodulator (inosine pranobex) and bacteriophage (staphylococcus, piofag) in patients with acute and chronic bacterial sinusitis. Materials and methods. A total of 60 patients aged 19 to 85 years who were ill with different forms of rhinosinusitis were examined. All patients were divided into two groups: up to I included 30 patients (control group), patients with acute bacterial rhinosinusitis who were on baseline therapy, which included antibacterial, pathogenetic, symptomatic, anti-inflammatory therapy of lysate bacteria, etc.), the second group consisted of 30 patients with a diagnosis of acute bacterial rhinosinusitis, to which baseline therapy was added immunomodulator (inоsine pranobex) and bacteriophage (staphylococcus or piofag). To study the factors of innate immunity, the absolute number of leukocytes and neutrophils of the peripheral blood was evaluated; the study of adaptive immunity factors included: determination of immunoglobulin A in serum, secretory IgA in nasal secret. Results. Out of 60 examined patients in 44, a complete clinical recovery (73.3 %) was achieved during this period. In 16 patients, the complete resolution of the symptoms after 12 weeks of treatment was not marked, that is, it was stated the transition of acute bacterial rhinosinusitis to the chronic form. The level of chronization was 26.7 %. In the group of patients treated with baseline therapy, after 12 weeks, sIgA concentration was observed at 22.5 %, IgA was 17.6 % (from 30 heifers per 12 months for 16 patients with chronic rhinosinusitis 53.3 %), IgA and in the group of patients with the addition of an immunomodulator and bacteriophage sIgA an increase of 4.4 times, IgA in 2.8 times from 30 heifers on acute bacterial rhinosinusitis in 12 weeks, the transition to chronic form was not. Conclusions. In the treatment of patients with rhinosinusitis, baseline drugs observed a low response of the immune system and prolonged course of the disease, as opposed to patients who received immunomodulatory drug and bacteriophage (staphylococcus or piofag, depending on the microflora) to the baseline therapy; this allowed a 4.3-fold increase in the concentration of sIgA and a 2.7-fold increase in the concentration of IgA, that is, to achieve a sufficient level of immune response. The therapeutic effect obtained with the addition of an immunomodulating agent and a bacteriophage (staphylococcus or piofag, depending on the microflora) to the basic therapy of treatment, is the basis for a more in-depth study of the mechanisms of action of these drugs in the treatment of patients with rhinosinusitis to reduce the chronization of the process. Key words: secretory immunoglobulin, bacteriophage, rhinosinusitis, chronic rhinosinusitis, local immunity.